An experimentally-accurate and complete room-temperature infrared HCN line-list for the HITRAN database. (August 2021) - Mellau, Georg Ch.; Makhnev, Vladimir Yu.; Gordon, Iouli E.; Zobov, Nikolay F.; Tennyson, Jonathan; Polyansky, Oleg L.
Highlights: Experimentally accurate HCN line list between vibrational states up to 10, 300 cm − 1 . Line list includes all vibrational states up to 7000 cm − 1 . HITRAN sensitivity limit for all rotational manifolds. High quality visual validation method of the line list with measured spectra. Abstract: A hydrogen cyanide line list (MOMeNT-90) developed for the HITRAN spectroscopic database covering 0–7500 cm − 1 range ( λ > 1330  nm) is presented. The line list is a combination of the variationally calculated line intensities with line centers obtained from experimentally derived energy levels. There are four features of this line list which distinguishes it from the previously calculated ones. First, the intensities are variationally calculated using a new, high-accuracy potential energy surface (PES) obtained via fitting the PES using experimental energy levels. Second, a new ab initio dipole moment surface was calculated at a high level of quantum chemical theory. Based on the wave functions calculated with the new PES and use of the new dipole moment surface, line intensities are reported which of similar accuracy to those obtained experimentally. Third, the calculated states are mapped to the existing complete set of experimental eigenenergies, resulting in an assigned and complete HCN line list down to the HITRAN intensity threshold of 10 − 34  cm/molecule. Fourth, extensive validation of the line list is provided through line-by-line comparisons of the results with measured HCN spectra which confirms the accuracy of the intensities used to construct the line list. The line list is augmented with parameters needed to calculate line widths for pressure-dependent simulations.